PENINGKATAN KAPASITAS PERANGKAT DESA DALAM MEMBANGUN KESADARAN MEMAHAMI SUSUNAN ORGANISASI DAN TATA KERJA (SOTK) - Abdul Aziz Zulhakim; Susanti, Is (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
One of the important instruments that form the basis for the performance of the village government is the Structure of Organisation and Work Procedure (SOTK). Permendagri No. 84/2015 is the main reference for the establishment of the SOTK of the village government. Therefore, to overcome this lack of understanding, it is necessary to empower the village officials through training and mentoring. In the implementation of this activity, the concept of participatory learning and action was adopted (Theresia in Hasanah & Saruri, 2018). This approach is implemented by emphasizing lectures, discussions, and brainstorming activities that are carried out interactively with the village head and village apparatus of Bioa Sengok, and continued with real actions or activities related to community empowerment material. This community service activity was carried out and produced knowledge for the Bioa Sengok village government in the form of capacity building in recognizing villages through the Village Law, understanding village government management, and understanding basic concepts of SOTK. However, in the future, more specific training for the village government is needed to organize good village governance.